Surgical Repair of a Median Cleft of the Upper Lip via a Pfeifer Incision: A Case Report - Rajeev Pandey; Rajat Gupta; Nitin Bhagat; Aviral Verma (Tehran University of Medical Sciences, 2016)
Median cleft is the midline cleft of the lip. It develops due to incomplete or failed fusion of the median nasal prominence. It can present with minimal deformities such as involvement of the vermilion border, or complex clefting of the midline structures and brain. Median clefts are broadly classified as true and false clefts. This case report describes a rare case of median cleft of the upper lip involving the white roll, which was not associated with any other deformities. Treatment included reconstruction of the philtrum and the cupid's bow while maintaining vermilion fullness and continuity, and minimizing scar formation. Various techniques have been advocated for treatment of this type of median upper lip cleft. Here we describe a technique using Pfeifer incision to correct our patient's defect. Pfeifer incision consists of wavy lines and its use has been advocated for correction of various craniofacial abnormalities. Keywords: Median Cleft Lip; Hypertelorism; Craniofacial Abnormalities